Single Dose Intravenous Tranexamic Acid Efficacy in Reducing Blood Loss in Total Hip Replacement: Intravenous Tranexamic Acid Efficacy in Total Hip Replacement - Zafir, Muhammad Badar Ud Din; Ronaq, Rana Shahid Waseem; Ali, Mazhar; Tariq, Mukhtar Ahmad; Ahmad, Israr (Pakistan Journal of Health Sciences, 2025)
Total Hip Replacement is a commonly performed procedure for Hip joint degeneration. Despite its hazards, blood transfusion has to be performed due to significant perioperative blood loss. The effects of pre-operative intravenous single-dose tranexamic acid in our population have been presented in this study. Objectives: To compare the mean blood loss during and after total hip replacement for hip osteoarthritis with or without a single dose of tranexamic acid. Methods: This quasi-experimental study was performed in the Orthopedic Surgery Department Unit II, Nishtar Medical University Hospital, Multan, from October 2022 to March 2024. In the experimental group, tranexamic acid (20mg/kg) was administered intravenously ten minutes before skin incision, while in the control group, no such drug was given. Preoperative and postoperative Hematocrit data were collected. THA was done as per standard protocol. The operative blood loss and blood transfusions were recorded and compared with the controls. Results: Among 60 patients, the mean age was 54.85 ± 12.23 years. Male were 19 (31.7%) and female were 41 (68.3%). BMI was 26.04 ± 3.48 Kg/m2. Mean age (p=0.746), mean BMI (p=0.633), age (p=0.417), gender (p=0.781) and BMI (p=0.749) were comparable in both groups. The estimated total loss of blood was significantly less in patients receiving intravenous tranexamic acid (1169.10 ± 191.92ml vs. 1730.07 ± 203.62ml; p<0.001) as compared to the control group. Conclusions: It was concluded that a pre-operative intravenous single dose of tranexamic acid decreased blood loss during surgery significantly in patients having total hip arthroplasty regardless of gender, age and BMI.